Advancing energy innovations: Reflections on 2024, prospects for 2025 - Oscar Acevedo (TESEA, Transactions on Energy Systems and Engineering Applications)
This editorial reflects on key points in the energy transition during 2024, including renewable energy growth, advancements in energy storage, and the rise of electric mobility. It also introduces special sections featuring research from the 2023 IEEE Colombian Caribbean and ICARGET Conferences. Looking ahead to 2025, it highlights the transformative roles of artificial intelligence, green hydrogen, and smart cities in shaping a sustainable energy future, reaffirming the journal’s commitment to driving innovation and global energy progress.